Medical tourism in Poland: the perspective and experience of the physicians - Mateusz Jankowski; Wojciech Stefan Zgliczyński; Bartosz Kobuszewski; Janusz Sytnik-Czetwertyński; Adam Skowron; Jarosław Pinkas; Dorota Cianciara (Wiedza Medyczna, 2020)
Introduction: Medical tourism is gaining popularity all over the world.  This term in this paper refers to patients of Polish nationality living abroad but using health services in Poland as well as foreign patients who use health services in Poland.Objective of the paper: The objective of this study was to investigate the magnitude and characteristics of medical tourism in Poland from the perspective of the physicians.Material and methods: a questionnaire-based survey was conducted among 700 physicians in Poland. The questionnaire included 29 questions regarding healthcare services in Poland.Results: Completed questionnaires were obtained from 498 physicians (67.9% females; average age 41.8±10.5 years), with a response rate of 71.1%. Clinical encounter with a Polish patient who resides on permanent basis outside the country was declared by 67.5% of respondents. There were significant differences (p<0.05) in the frequency of domestic medical tourism depending on the medical education level as well as practice type. Most of the participants (72.3%) declared an encounter with a foreign patient who has used health services in Poland. Except the urgent health need, as factors determining domestic or international medical tourism, the doctors mentioned: quality of healthcare services, price competitiveness as well as the possibility of combining treatment with a visit to the family.Conclusions: Most physicians in Poland have had the opportunity to consult a patient who has used health services as part of national or international medical tourism.